Philological and historical commentary on Ammianus Marcellinus XXVI - Boeft, J. den. (Philological and Historical Commentary on Ammianus Marcellinus, 2008)
Book 26 of Ammianus' Res Gestae is the first of the hexad which deals with the rule of the emperors Valentinian and Valens (364-378). In the first five chapters Ammianus describes the election of Valentinian, who appointed his brother Valens as his co-ruler, and subsequently divided the empire into an eastern and a western part. The next chapters deal with the revolt of Procopius. They offer the most detailed account of a coup d' état in Roman historiography. The memory of Julian, whose death was the central theme of the preceding book, is still very much alive. None of the three protagonists of Book 26 was remotely his equal. His loss meant a turn for the worse in the history of Rome.